Flexible Models for Stock Returns Based on Student's T Distribution. - Afuecheta, Emmanuel; Chan, Stephen; Nadarajah, Saralees (Manchester School (1463-6786), 2019)
Models based on the Student's t distribution are proposed with its scale parameter randomized. Mathematical properties of the models such as their probability density functions, cumulative distribution functions, moments and characteristic functions are derived. Three of the models are fitted to daily log returns of six financial indices. They were shown to provide better fits than mixtures of Student's t distributions and the popular generalized hyperbolic distribution.